A model of Islamic leadership based on Hasan Banna's writings - Mamat, Ismail; Noor, Haji, Anuar Sadat (Zes Rokman Resources, 2017)
Leadership has long been an often-discussed topic among intellectuals of a variety of disciplines. Analysis of leadership is often centered on day-to-day practices of particular organizations. Leadership is defined by many scholars and researchers, such as a process of whereby an individual influences a group of individuals to achieve a common goal. In Islam, leadership is a process of inspiring and coaching voluntary followers in an effort to achieve a clear and defined shared vision. It is seen as human factors that bind a group together and motivate it toward desired goals. Hence, in Islam, a leader is not free to act as he or she chooses, nor must he submit to the wishes of any group, he or she must act only to implement Allah’s laws on earth. Allah says: “And We made them leaders guiding men by Our command and We sent inspiration to do good deeds, to establish regular prayers, and to practice regular charity; and they constantly served Us only” (Surah Al-Anbiya’, [21] 73). The purpose of this article is to address the model of leadership in Islamic organizations or movements, particularly practiced by a well-known Islamic organization in the Muslim world, namely Ikhwan Muslimin (IM) of Egypt. The paper highlights, too, that the nature and view of leadership, in the Islamic organizations or movements, should be in line with the teaching of Islam, based on the Qur’an and the sunnah as dual sources of Islamic conceptions of the role of a leader, and the doing of leadership. The Qur’an is the holy book of Islam and the foundational constitution of Muslims around the world. The sunnah concerns the life of the Prophet Muhammad, which Muslims are encouraged to emulate; and this exemplary life is largely understood through the hadith, which preserve his words and deed.